Accurate tuning of ordered nanotubular platinum electrodes by galvanic plating - Roscher, Valentin; Licklederer, Markus; Schumacher, Johannes; Rios, Grisell Reyes; Hoffmann, Bjoern; Christiansen, Silke; Bachmann, Julien (Dalton Transactions, 2014)
Platinum nanotubes are created by galvanic deposition inside porous templates. The effects of the electrolyte's ion concentration and pH, of the applied potential and of the deposition duration on the morphology of the tubes are investigated systematically. The system provides a model electrode platform with accurately tunable geometry for the fundamental investigation of electrochemical transformations. For slow electrochemical reactions, we observe a linear increase of the galvanic current with the length of the nanotubes, and therefore with the specific surface area of the electrode. In contrast to this, inherently fast electrochemical transformations are diffusion-limited and give rise to the same current density independently of the geometry. These results delineate a strategy for optimizing the performance of electrochemical energy conversion devices systematically via nanostructuring the electrode surfaces.

An electrochemically functional layer of hydrogenase extract on an electrode of large and tunable specific surface area - Schlicht, Stefanie; Assaud, Loic; Hansen, Moritz; Licklederer, Markus; Bechelany, Mikhael; Perner, Mirjam; Bachmann, Julien (Journal of Materials Chemistry A, 2016)
Electrode supports are generated by electrospinning of polyacrylonitrile fibers and subsequent coating of a thin electrically conductive TiO2 layer by atomic layer deposition. The supports are then functionalized with a [NiFe]-hydrogenase-containing membrane fraction from Escherichia coli and are characterized structurally and electrochemically. The hydrogenase suspension generates a micron-thick organic film around the fiber mat, which exhibits electrocatalytic activity for hydrogen evolution. Furthermore, the electrode geometric surface area is varied systematically via the electrospinning procedure, which reduces the charge transfer resistance and increases the hydrogen evolution current density to > 500 mu A cm(-2) at 0.3 V overpotential.

Dewetted Au Nanoparticles on TiO2 Surfaces: Evidence of a Size-Independent Plasmonic Photoelectrochemical Response - Licklederer, Markus; Mohammadi, Reza; Nguyen, Nhat Truong; Park, Hyoungwon; Hejazi, Seyedsina; Halik, Marcus; Vogel, Nicolas; Altomare, Marco; Schmuki, Patrik (Journal of Physical Chemistry C, 2019)
We induce solid-state dewetting of thin Au films (nominal thickness of 0.5-10 nm) on flat TiO2 surfaces to produce Au nanoparticles with an average size tunable in the 3-200 nm range. Such Au-decorated TiO2 surfaces enable plasmonic photoelectrochemical water splitting under visible light illumination (450-750 nm), with a photon-to-current conversion efficiency that reaches a maximum for TiO2 surfaces decorated with similar to 30 nm sized Au particles. Optical measurements show, as expected, a red shift of the plasmon resonance with the increasing Au nanoparticle size. More interestingly, the photocurrent is found to peak for every photoanode at similar to 600 nm regardless of the Au nanoparticle size, i.e., the wavelength of maximum photocurrent is size-independent. Such a remarkable observation can be ascribed to a hot electron injection cutoff effect, i.e., can be explained in terms of the interband versus intraband transition scenario.
CRIS-Team WoS Importer:2019-07-30

Intrinsic Au-decoration on anodic TiO2 nanotubes grown from metastable Ti-Au sputtered alloys-High density co-catalyst decoration enhances the photocatalytic H-2 evolution - Hejazi, Seyedsina; Altomare, Marco; Nguyen, Nhat Truong; Mohajernia, Shiva; Licklederer, Markus; Schmuki, Patrik (Applied Materials Today, 2019)
Recent work demonstrated that intrinsic Au nanoparticle decoration of TiO2 nanotube arrays (NTs) can be achieved by electrochemical anodization of Ti-Au alloy substrates. However, for a Ti-Au cast alloy produced by melt-alloying, the Au concentration cannot exceed the solubility limit of Au in Ti of 0.2 at.% - this sets constraints on the intrinsic Au nanoparticle loading on anodic TiO2 NTs. Here we explore "metastable" Ti-Au metal substrates that are produced by Ti and Au cosputtering and we establish Au concentrations that far exceed the solubility limit in cast Ti-Au alloys. We show the use of these "metastable" Ti-Au sputtered layers for the anodic formation of TiO2 NTs with a much higher density of Au nanoparticle loading than using classic alloys. Under optimized conditions (Au nanoparticle density) photocatalytic H-2 production from such Au@TiO2 platforms provides a 15 times higher photocatalytic H-2 evolution rate than the best rates achieved with conventional alloys. (C) 2018 Elsevier Ltd. All rights reserved.
CRIS-Team WoS Importer:2019-02-27

Ordered nanotubular titanium disulfide (TiS2) structures: Synthesis and use as counter electrodes in dye sensitized solar cells (DSSCs) - Licklederer, Markus; Cha, Gi; Hahn, Robert; Schmuki, Patrik (Journal of The Electrochemical Society, 2019)
TiS2 nanotubular structures were synthesized by a high temperature H2S treatment of anodized TiO2 nanotube layers, and their electrochemical activity for a use as counter electrodes in dye sensitized solar cells (DSSCs) was evaluated. During conversion to TiS2 compositional, morphological and structural transformations were monitored. The fully converted TiS2 nanostructures show a high electrocatalytic activity for the I-/I3-oxidation comparable to a nanoparticular platinum layer. For a simplified model a DSSC solar cell efficiency of 6.1% was obtained using the TiS2 nanotube layer as counter electrode, which is very close to values obtained for a Pt reference (6.2%).
CRIS-Team Scopus Importer:2020-02-21